Optimization of Offshore Windfarm Cable Layouts - Alabaş Uslu, Çiğdem; ÜLKÜ, İLAYDA (My University, 2018)
As renewable energy arises to be an alternative energy source around the world, installation of the wind farms increases in the areas where the wind potential is efficient. One of the design problems in the installation of wind farms is determination of cable connections between turbines and transmitter(s) to provide the flow of generated energy from each turbine to the transmitter(s) through one or more routes. While layout of turbines should minimize wake losses to provide maximum of energy production, layout of cables should provide gathering of total energy at one or more transmitters minimizing total cost of cables. The present study takes layout of a set of turbines and a single transmitter as input data and addresses the optimization of cable layout problem to minimize of total cost of cables which can be different in types and capacities. The problem is modeled as a mixed integer linear program and optimal solutions or feasible solutions are obtained to a set of test instances using the proposed model. Experiments show that the instances can be optimized up to 20 turbines and feasible solutions are available for the larger problems.
Keywords: Mixed-integer Linear Programming; Cable Layoud; Cable Routing; Wind Farm Optimization